CGIAR Initiative on Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion (SAPLING): IPSR Innovation Portfolio Management Report - Baltenweck, Isabelle; Rekik, Mourad; Ouma, Emily A.; Galiè, Alessandra; Kassie, Girma T.; Notenbaert, An Maria Omer; Okeyo Mwai, Ally; Haile, Aynalem; Dione, Michel M.; Wamatu, Jane; Thierfelder, Christian L.; Varijakshapanicker, Padmakumar; et al. (CGIAR System Organization, 2023)
CGIAR Research Initiative on Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion aims to transform the livestock sector in Ethiopia, Kenya, Mali, Nepal, Uganda, Tanzania, and Vietnam, with the objective of enhancing productivity, resilience, equity, and sustainability. This goal will be accomplished by developing new technologies and practices and adapting existing ones to bolster sustainable livestock production. Additionally, the initiative will encourage innovative practices for the safe consumption of livestock-derived foods as part of diverse diets. Gender equity and social inclusion will be prioritised, and efforts will be made to promote competitive and inclusive livestock value chains. The initiative will also generate and consolidate evidence, as well as scalable models and tools. This report offers an overview of the portfolio of innovations of the initiative and its partners.